2011
DOI: 10.1097/bot.0b013e3181e31ccc
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Proximal Femoral Locking Compression Plate: A Case Series

Abstract: Biomechanical studies have shown the PF-LCP to be stronger or equivalent to other fixation methods for fractures of the femoral neck and subtrochanteric femur fractures. The seven failures in our cases may be partially the result of patient factors as well as technical factors; however, there appears to be a high rate of failure even when surgery is performed by experienced and fellowship-trained traumatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 6 publications
3
84
2
Order By: Relevance
“…Glassner in his study stated that five of the seven cases treated with locking plate developed complications and device failure after 12.7 days, in average [10]. Our study is also partly consistent with Glassner's results; as 44 % of the patients experienced complications during the first 10 days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Glassner in his study stated that five of the seven cases treated with locking plate developed complications and device failure after 12.7 days, in average [10]. Our study is also partly consistent with Glassner's results; as 44 % of the patients experienced complications during the first 10 days.…”
Section: Discussionsupporting
confidence: 91%
“…It is attributed to the stiffness of this tool that prevents any fracture site micromotion, placing the mechanical burden on the implant, which can result in failure at the bonescrew interface or fatigue failure of the implant itself [9]. In Glassner's study, seven treatment failures with the locking plate were due to nonunion, implant fracture, and loss of fixation [10]. Generally, different causes for this issue are intended.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this the PFLCP act as angular stable devices and provide rigid fixation. But they are associated with a higher number of varus collapse and implant failure [13,14]. To overcome this problem the reverse-DFLCP of the contralateral side has been advocated by some authors, as it provides an added number of screw options for proximal femoral fracture fragment, resulting in a more stable construct [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Due to higher failure rates of proximal femoral locking compression plate [13,14], some authors advocated the use of reverse distal femoral locking compression plate (reverse-DFLCP) of the contralateral side for intertrochanteric fractures, as it provided an added number of screw options for proximal femoral fracture fragments, thus resulting in a more stable construct with higher pull out resistance [15][16][17]. Clinical studies have also showed good results of reverse-DFLCP when compared to intramedullary devices [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Concluded that seven failures in their cases may be partially the result of patient factors as well as technical factors; however, there appears to be a high rate of failure even when surgery is performed by experienced and fellowship-trained traumatologists. 25 In 2011 Zhongguo Gu Shang et al in comparative study of intertrochanteric fractures treated with proximal femur locking compress plate in elderly patients and compared the clinical outcomes of dynamic hip screw (DHS), intramedullary fixation (IF) and proximal femur locking plate (PF-LCP) in the treatment of 165 old patients with intertrochanteric fractures were treated respectively by DHS, IF, PF-LCP. There were58 DHS, 65 IF and 42 PF-LCP cases in study.…”
mentioning
confidence: 99%